Pengaruh Komunikasi Interpersonal Guru Terhadap Minat Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Kristen Dan Budi Pekerti Kelas VIII SMP Negeri 1 Sipoholon - Arneta Bunga Ria Siahaan; Hasudungan Simatupang; Elsina Sihombing; Oktober Tua Aritonang; Andar Gunawan Pasaribu (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the positive and significant influence of teachers' interpersonal communication on students' interest in learning in the Christian Religious Education and Character Education subjects for class VIII, even semester of SMP Negeri 1 Sipoholon for the 2022/2023 academic year. The research method is quantitative with a descriptive inferential approach. The population is all students in class VIII of SMP Negeri 1 Sipoholon for the 2022/2023 academic year, totaling 190 people and a sample of 32 people was determined using the probability sampling method with simple random sampling type. Data was collected using a positive closed questionnaire with 32 items. The results of data analysis show that there is a positive and significant influence of teacher interpersonal communication on students' interest in learning in the subjects of Christian Religious Education and Character Education in class VIII, even semester of SMP Negeri 1 Sipoholon for the 2022/2023 academic year: 1) Test the analysis requirements: a) test The positive relationship obtained is rxy = 0.593 > rtable(a=0.05,n=32) = 0.349. b) Testing a significant relationship obtained tcount= 4.037 > ttable(a=0.05,dk=n-2=30)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="21","28"+0.58X. b) Regression coefficient of determination test (r2) = 35.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=14, dk denominator=n-2=32-2=30) namely 16.28 > 2.01. Thus Ha is accepted and H0 is rejected.